Genomics of Obsessive-Compulsive Disorder—Toward Personalized Medicine in the Era of Big Data - Szejko, Natalia; Dunalska, Anna; Lombroso, Adam; McGuire, Joseph F.; Piacentini, John (Frontiers in Pediatrics, 2021)
Pathogenesis of obsessive-compulsive disorder (OCD) mainly involves dysregulation of serotonergic neurotransmission, but a number of other factors are involved. Genetic underprints of OCD fall under the category of “common disease common variant hypothesis”, that suggests that if a disease that is heritable is common in the population (a prevalence greater than 1–5%), then the genetic contributors – specific variations in the genetic code – will also be common in the population. Therefore, the genetic contribution in OCD is believed to come from multiple genes simultaneously and it is considered a polygenic disorder. Genomics offers a number of advanced tools to determine causal relationship between the exposure and the outcome of interest. Particularly, methods such as polygenic risk score or Mendelian Randomization enable investigation of new pathways involved in OCD pathogenesis. This premise is also facilitated by the existence of publicly available databases that include vast study samples. Examples include population-based studies such as UK Biobank, China Kadoorie Biobank, Qatar Biobank, All of US Program sponsored by National Institute of Health or Generations launched by Yale University, as well as disease-specific databases, that include patients with OCD and co-existing pathologies, with the following examples: Psychiatric Genomics Consortium, ENIGMA OCD, The International OCD Foundation Genetics Collaborative or OCD Collaborative Genetic Association Study. The aim of this review is to present a comprehensive overview of the available Big Data resources for the study of OCD pathogenesis in the context of genomics and demonstrate that OCD should be considered a disorder which requires the approaches offered by personalized medicine.